Treatment Intensification With Insulin Pumps and Other Technologies in Patients With Type 2 Diabetes: Results of a Physician Survey in the United States - Grunberger, George (Clin Diabetes, 2020)
An online survey was conducted to assess the perspectives and use of diabetes technologies by a sample of U.S. primary care physicians (PCPs) and endocrinologists to optimize intensive insulin therapy in patients with type 2 diabetes. Overall, endocrinologists reported using diabetes technologies more frequently than PCPs for patients with type 2 diabetes requiring basal-bolus insulin therapy. PCPs and endocrinologists who were highly focused on diabetes management with insulin therapy reported using insulin delivery devices (insulin pumps and wearable tube-free patches) when patients are not achieving their A1C target while taking basal plus three or more prandial injections of insulin daily.